PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL (Studi Pada SMP Negeri Se-Kecamatan Ulujami Kabupaten Pemalang) - Jamal Abdul Azis, 1352020044; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the effect of transformational leadership and motivation to work on teacher performance moderated by the organizational culture. The specific objectives of the study was to examine and analyze the influence of transformational leadership on teacher performance, the effect of work motivation on teacher performance, the influence of organizational culture on teacher performance, organizational culture moderates the influence of transformational leadership on teacher performance, and organizational culture moderated the effect of motivation to work on teacher performance. This research is an explanatory research study that proves the influence of transformational leadership and motivation to work on teacher performance organiza-tional culture moderated. This study uses the study population (census) amounted to 117 respondents. Data of this research is primary data obtained directly from the source. The method of data analysis using a model of moderation with a quasitype interaction techniques. The results showed that transformational leadership positive and significant impact on teacher performance, motivation positive and significant impact on teacher performance, organizational culture does not influence the performance of teachers, organizational culture does not moderate the influence of transformational leadership on teacher performance, and organizational culture moderated the effect of work motivation on teacher performance.Keywords: Transformational Leadership, Motivation, Teacher Performance, Organizational Culture